Islam, the West, and Tolerance - Tyler, A. author. aut Link
IX, 219 p.
Keywords: This book provides an honest assessment of the contemporary relationship between Western and Islamic cultures and puts forth the cross-cultural idea of tolerance as one invaluable approach for affecting peaceful coexistence.